Catalytic transfer hydrogenation of levulinic acid to γ-valerolactone over a bifunctional tin catalyst. Issue 2 (4th January 2017) - Xu, Shaodan; Yu, Deqing; Ye, Tao; Tian, Panpan
Abstract : Efficient conversion of levulinic acid to γ-valerolactone over a bifunctional Sn catalyst under catalytic transfer hydrogenation. Abstract : The conversion of biomass-derived levulinic acid (LA) to γ-valerolactone (GVL) is important but extremely challenging due to the use of noble metal catalysts and high-pressure gaseous hydrogen. Here we describe the transfer hydrogenation of LA to GVL using 2-propanol as hydrogen donor over a Sn modified silica catalyst (SnO2 /SBA-15) which gives high LA conversion (85.1%) and GVL selectivity (95.2%). Key to this success is employing a simply synthesized Sn-modified silica catalyst (SnO2 /SBA-15) with both Lewis and Brønsted acidity, which could synergistically catalyze the tandem steps of hydrogen transfer and esterification, leading to successful transformation of LA to GVL.